2008
DOI: 10.1007/s00431-008-0743-9
|View full text |Cite
|
Sign up to set email alerts
|

A further case of renal tubular dysgenesis surviving the neonatal period

Abstract: Renal tubular dysgenesis is a critical disorder characterized by the Potter phenotype and severe hypotension in the early neonatal period. We herein report a 3-year-old female with renal tubular dysgenesis. Endocrinological studies showed a high plasma renin activity (over 49.2 ng/ml/h; normal range 2.0-15.2), high active renin concentration (1,823.5 pg/ml; normal range 2.4-21.9), and low angiotensin-converting enzyme (ACE) concentration (1.7 U/l; normal range 8.3-21.4). Taken together, these findings suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 9 publications
3
36
1
Order By: Relevance
“…Mutations in the RAS genes are reported in 15 families [Bacchetta et al, 2007;Ben Amar et al, 2007;Danilov et al, 2010;Gribouval et al, 2005;Michaud et al, 2011;Schreiber et al, 2010;Uematsu et al, 2006Uematsu et al, , 2009Zingg-Schenk et al, 2008] and new sequence changes identified in our laboratory in 33 families are presented in Table 1. New mutations were identified by direct sequence analysis as described previously [Gribouval et al, 2005].…”
Section: Mutations In the Ras Genesmentioning
confidence: 89%
See 3 more Smart Citations
“…Mutations in the RAS genes are reported in 15 families [Bacchetta et al, 2007;Ben Amar et al, 2007;Danilov et al, 2010;Gribouval et al, 2005;Michaud et al, 2011;Schreiber et al, 2010;Uematsu et al, 2006Uematsu et al, , 2009Zingg-Schenk et al, 2008] and new sequence changes identified in our laboratory in 33 families are presented in Table 1. New mutations were identified by direct sequence analysis as described previously [Gribouval et al, 2005].…”
Section: Mutations In the Ras Genesmentioning
confidence: 89%
“…All except those previously reported in four families [Danilov et al, 2010;Gribouval et al, 2005;Schreiber et al, 2010;Uematsu et al, 2009] were novel. Mutations were present in the homozygous state in 15 families, in the compound heterozygous state in 13, whereas only one heterozygous ACE mutation was identified in three families.…”
Section: Angiotensin-converting Enzyme Acementioning
confidence: 92%
See 2 more Smart Citations
“…Inherited RTD is caused by mutations in the genes encoding the components of the reninangiotensin system (RAS) [2]. Mutations in the genes encoding angiotensinogen (AGT), renin, angiotensinconverting enzyme (ACE), and angiotensin II receptor type 1 have been reported in several case reports [1,[3][4][5][6][7][8]. RTD is also associated with fetopathy induced by drugs such as angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin type 1 receptor blockers (ARBs) [9][10][11].…”
Section: Introductionmentioning
confidence: 98%